Numerical investigation of Heat Transfer Enhancement in Circular Tube using Twisted Tape Inserts and Nanotechnology - Najim Abid Jassim; Kamel Abdul Hussin; Noor Yahya Abdul Abbass (Wasit Journal of Engineering Sciences)
In the present work the analysis of three different width ratio of twisted tape in a shell and tube heat exchanger done by ANSYS FLUINT14.0. Heat exchanger type shell and tube have been widely used in industrial application such as refrigeration and environment protection, electrical power generation and chemical engineering. This work deals with the theoretical investigation, which was to evaluate the benefit of changing the width of twisted tape in the heat exchanger and the improving the heat transfer by using water as the working fluid in the first case, then using Nano fluids as a heat transfer working fluid. From the use of the condition in table (1) the simulation shows results of enhancement in heat transfer rate ranging from (53.24% to 55.55%) at width ratio 0.71, (53.62% to 56.09%) at width ratio 0.854 and (52.44% to 57.17%) at width ratio 1, for plain tube with twisted tape with respect to plain tube without twisted tape by using water as cooling fluid. By using Nano- fluid (AL2O3) the enhancement in heat transfer is (69.14% to 60.44%) at width ratio 0.71, (58.36% to 61.51%) at width ratio 0.854 and (56.76% to 63.35%) at width ratio1, for plain tube with twisted tape with respect to plain tube without twisted tape.